Colocalization of cortactin and PH domain of BCR in HEK293T cells and its potential role in cell signaling - Gurianov, D.S.; Antonenko, S.V.; Telegeev, G.D. (Вiopolymers and Cell, 2016)
Chromosomal translocation t(9;22)(q34;q11) leads to the generation of different types of the BCR-ABL fusion protein and cause different types of leukemias. The generated fusion proteins differ by the presence or absence of certain domains of BCR – C2, PH, and DH. The mass-spectrometric analysis identified 23 possible interaction partners of PH domain of BCR. Among them is cortactin (CTTN), which is a multidomain protein responsible for the actin branching during endocytosis. The activation of cortactin occurs after phosphorylation by SRC kinase. However, it is unknown whether ABL kinase can phosphorylate and activate CTTN in the same manner. Aim. To demonstrate whether CTTN and PH domain of BCR colocalize in HEK293T cells, to analyze possible phosphorylation sites for ABL kinase in the cortactin and to make a comparative prediction for SRC kinase. Methods. Cells HEK293T were transfected with the engineered pECFP-C3-CTTN and pmCitrine-C1-PH using a cationic polymer transfection and evaluated with fluorescent microscopy. Putative phosphorylation sites of CTTN by ABL and SRC kinases were predicted by GPS 2.1 software. Results. PH domain and CTTN were expressed in HEK293T cells and show specific cellular colocalization. The phoshorylation sites for Abl kinase (Y384, Y396, Y409, Y416, Y427, Y433, and Y449) were detected in the proline-rich region of CTTN and they match corresponded sites predicted for SRC kinase. Conclusions. We have shown that CTTN has cytoplasmic localization and PH domain of BCR localized predominantly but not exclusively in the nucleus. Their partial colocalization occurs in specific dot-like perinuclear regions. A potential phosphorylation of CTTN by ABL may be one of the activation pathways during leukemogenesis.